SABLON RESERVATION APPLICATIONS IN BRITISH INDIE BANNER USING VISUAL BASIC 6.0 - Widi Friandi; Cut Asiana Gemawati. Skom. MMSi Cut Asiana Gemawati. Skom. MMSi (Jurnal Sistem Informasi, 2010)
Already there is no doubt anymore that the use of computers at this time is needed.Not only the big companies, medium companies and small companies, need acomputer to support that in running its business.By using Microsoft Visual Basic 6.0, the authors tried to make an application tosimplify the design process booking transactions silk screening on British IndieBanner. With komputerisasinya process the transaction, expected to be storedreservation data properly and can accelerate the search process the data and toimprove the quality of care.